The adventures of Sherlock Holmes - Doyle, A. Conan (New York : Baronet Books, 1985)
Includes three Sherlock Holmes mystery adventures: "The Red-headed League," "The Adventure of the Speckled Band," and "The Adventure of the Copper Beeches."
Keywords: Mystery and detetive stories; Short stories